SCIENCE OF PEDAGOGY: WAYS OF RESEARCH OF PERSONNELS - Розман, Ирина (SWorldJournal, 2020)
The article considers the ways of research of pedagogical personalities. Particular attention is paid to highlighting the importance of methods of studying the experience of the scientist. It is noted that for a detailed study of pedagogical personality